PENDIDIKAN PRANIKAH BERBASIS KELUARGA PADA REMAJA PUTRI DI KECAMATAN DAMPAL SELATAN - Rus'an Rus'an; Hamzah Hamzah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2019)
Adolescence for girls takes place in the age of 12-21 years. This period is known as a time full of problems, not only foryoung women themselves, but also problems for parents, families, and their environment. Even further, post-marriagedisharmony in a household has a complex effect that results in the increasingly weakening of the quality of humanresources at a macro level. In adolescence the role of a mother is very important and primary because she is naturallygifted with subtle and gentle feelings, so it is more appropriate to be a coach for her teenage child who ispsychologically turbulent.Methodologically, there are two data collection techniques that will be used in this study, namely questionnaire and indepth interviews. The questionnaire filling will be accompanied by researchers. Thus the research error rate can bereduced as small as possible and the percentage of answers returned is higher. The interview was conducted informally.In this way the information obtained is expected to be more and more in-depth and more representative of the realsituation. Furthermore, the research data will be analyzed quantitatively and qualitatively. The quantitative analysisused is descriptive analysis such as percentages, averages, and modes. While the qualitative analysis applied is domainanalysis and taxonomic analysis.The results showed that in general the level of knowledge of housewives about premarital education for their youngwomen, was at the moderate level of 57.3% and low 23.3%. while in general the knowledge of young women aboutpremarital education is at the moderate level of 56.0% and low at 28.7%. Perceptions / attitudes of housewives towardspremarital for young women as much as 50.0% are low and 32.7% are moderate. Young girls' perceptions / attitudesabout premarital education were also generally low at 52.2% and moderate at 36.7%. Then, the role of familyinstitutions is generally of a moderate level, namely as much as 68.0% while those already classified as high are asmuch as 24.7%.